Evaluation Of Enzyme Immunoassays In The Diagnosis Of Duck Plague - Malmarugan S (Department of Microbiology, College of Veterinary and Animal Sciences, 1997)
Use of Enzyme immunoassays namely dot ELISA and plate ELISA were evaluated to detect DP viral antibodies in serum samples and in whole blood dried on filter paper strips and their efficacy was compared with standard passive haemagglutination test. Indirect immunoperoxidase test was also used to detect DP viral antigen in paraffin embedded liver and spleen. ASS at 33 per cent level was used for separation of duck globulins and antiduck globulins. The protein concentration of these globulins were 34 mg/ml and 15 mg/ml respectively. The purity of these globulins were tested by IEP and AGPT using antiduck whole serum raised in rabbits. Duck plague hyperimmune serum was raised in healthy ducklings with live attenuated DP vaccine having a virus titre of 3.5 log10 ELD50/0.5 ml. This serum was used as the positive control. A total of 200 serum samples, 35 liver and 30 spleen samples were collected from different localities for the detection of duck plague viral antibodies and antigen. Corresponding blood samples were also collected on filter paper strips and the serum was eluted and ELISA was carried